2013
DOI: 10.1177/1555412013493349
|View full text |Cite
|
Sign up to set email alerts
|

Is the Video Game a Cultural Vehicle?

Abstract: Following the exportation of Japanese media products such as TV dramas, Japanese culture and products have swept across many Asian countries, especially Taiwan. Based on the historical background and unique characteristics of games, this study investigates the cultural effect of Japanese video games on players in Taiwan. This study also presents an analysis of the differences between TV and the video game as cultural vehicles. We used both quantitative and qualitative methods. Results indicate a relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
0
19
0
3
Order By: Relevance
“…This concept of “real enough” becomes all the more important when one considers that Chen found individuals' cultural attitudes can be and are shaped by the games they play. In this mixed method study, Chen found that people living in Taiwan had an increased interest in and desire to adopt cultural attitudes of Japan after playing Japanese games. This demonstrates the persuasive power of games.…”
Section: Simulation Games and Playmentioning
confidence: 99%
“…This concept of “real enough” becomes all the more important when one considers that Chen found individuals' cultural attitudes can be and are shaped by the games they play. In this mixed method study, Chen found that people living in Taiwan had an increased interest in and desire to adopt cultural attitudes of Japan after playing Japanese games. This demonstrates the persuasive power of games.…”
Section: Simulation Games and Playmentioning
confidence: 99%
“…Scholars have suggested that video games are cultural texts in their own right, featuring interactive learning and visual storytelling (Buckingham & Burn, ; Salen, ). Cultural texts can be defined as literary products of a society that are in turn instigators of culture that communicate meaning (Chen, ; Steinkuehler, ). Examples include J.R.R.…”
Section: Games Culture and Learningmentioning
confidence: 99%
“…A study by Chang and Zhang (2008) investigated the significance of materialism in influencing attitudes and motivation to play online games, but it is still uncertain whether playing games affects players' values regarding consumerism. Meanwhile, other studies indicate playing games does affect consumption preference in which heavy players' preference for consuming media products from Japan were higher than mild and light players (Chen, 2013). Thus, it is hypothesized that heavy dress up players will be more materialistic than those who do not play as heavily.…”
Section: Games and Materialismmentioning
confidence: 99%